Effect of laser processing parameters on the efficiency of material: a review in industrial application field - Sabri Salim, Muhammed Sabri; Sabri, Naseer; K. Ibrahim, T.; M. Noaman, Noaman; N. Akram, Israa; Hashim Latif, Israa (International Journal of Engineering and Technology, 2019)
There is considerable interest in reducing the cost of alloy components that are highly resistant to corrosion. Therefore, low-cost laser energy was used compared to other treatments, where this energy was used to enhance surface resistance of the alloy. In this paper, the advantages of surface treatment using laser energy have demonstrated, in addition, analysis of the effect of the treatment parameters on the material properties. Surface treatment methods for laser materials were classified in thermal processes and thermal chemical processes. The chemical thermal process shows a change in the surface composition of the treated material. The initial state of hydration for cement paste can be identified by analyzing the changes resulting from the intensity of the laser processor. Alumina samples in Ceram proved more soluble areas and became more homogenous and smooth with fewer openings and cracks, especially with energy higher than 10 W CO2 and higher power density than Excimer 6.2 J / cm laser devices. The optimum power of the laser used to remove the material is 40-200 W / cm2.Â